STRATEGI PENGEMBANGAN PERUSAHAAN DAN SDM BAGIAN QUALITY CONTROL PTPN XI PG WRINGIN ANOM KABUPATEN SITUBONDO - Handa Aprisco (UPT Penerbitan Universitas Jember, 2018)
This research is aims to explore the potential of plants as sugarcane processing agribusinesses and one of the most important sectors in the sugar industry in Indonesia currently has a lot of attention to business dynamics. Therefore, this study was carried out in PTPN XI PG. Wringin Anom by reviewing about improving the quality of human resources that can be done with one of the proper HR learning functions and company analysis by looking at internal and external factors of the company with SWOT analysis. This study aims to: (1) How to develop the quality of HR PG Wringin Anom Quality Control ? (2) How is the role of In House Training on the development of HR quality PG. Wringin Anom? (3) How is the opportunity and corporate development strategy of PG. Wringin Anom? The results showed that: (1) Teaching quality of HR PG Wringin Anom's quality control section through In House Training (2) In House Training as the development of HR PG. Wringin Anom quality big welcomes the dynamics of competition both domestically and international (3) Opportunity of PG. Wringin Anom is located in quadrant 1 with a matrix position (3.90; 3.25) matrix area of ​​12.7 which means the company has strong and opportunity competition